2012
DOI: 10.1182/blood.v120.21.712.712
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Mutational and Cytogenetic Analysis Identifies New Prognostic Subgroups in Chronic Lymphocytic Leukemia

Abstract: 712 The identification of NOTCH1, SF3B1, MYD88 and BIRC3 genetic lesions in chronic lymphocytic leukemia (CLL) prompts a comprehensive and dynamic prognostic algorithm including gene mutations, chromosomal abnormalities, and their changes during clonal evolution. The study utilized both time-fixed (637 newly diagnosed CLL) and time-dependent (257 CLL provided with 524 sequential samples) approaches. Each sample was investigated for TP53, NOTCH1, SF3B1, MYD88, and BIRC3 mutations by Sanger sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 37 publications
0
66
1
Order By: Relevance
“…Among these IGHV-M patients, MYD88 L265P status appears to be associated with worse OS. In previous studies that do not mention controlling for IGHV status, one reported higher incidence of MYD88 L265P patients in advanced clinical stages (Puente et al, 2011); another reported an association with better OS and longer time to first treatment (TTFT) (Martinez-Trillos et al, 2014); and the rest did not find an association with progression or survival (Puente et al, 2011;Rossi et al, 2013). The only other study to our knowledge that did control for IGHV status reported a tendency to shorter TTFT in later-stage MYD88 L265P cases but no association with TTFT or OS in Binet Stage A cases (Baliakas et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Among these IGHV-M patients, MYD88 L265P status appears to be associated with worse OS. In previous studies that do not mention controlling for IGHV status, one reported higher incidence of MYD88 L265P patients in advanced clinical stages (Puente et al, 2011); another reported an association with better OS and longer time to first treatment (TTFT) (Martinez-Trillos et al, 2014); and the rest did not find an association with progression or survival (Puente et al, 2011;Rossi et al, 2013). The only other study to our knowledge that did control for IGHV status reported a tendency to shorter TTFT in later-stage MYD88 L265P cases but no association with TTFT or OS in Binet Stage A cases (Baliakas et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Rare mutations in TRAF2 and TRAF3 were also described in CLL. BIRC3 mutations are strongly associated with unmutated IGHV CLL, ATM mutations 11q deletion and shorter TTFT (Rose-Zerilli et al, 2011;Rossi et al, 2013;Baliakas et al, 2015). The frequency of BIRC3 mutations is approximately 3-8% at the time of diagnosis but mutations may emerge over time (Rose-Zerilli et al, 2011;Rossi et al, 2012b;Cortese et al, 2014;Baliakas et al, 2015;Puente et al, 2015).…”
Section: Nfκb Pathwaymentioning
confidence: 99%
“…The last few years have seen tremendous advances in understanding the genomic landscape, clonal architecture and evolution of the chronic lymphocytic leukaemia (CLL) genome (Braggio et al, 2012;Quesada et al, 2012;Schuh et al, 2012;Landau et al, 2013). Significant efforts are already underway in understand the clinical implications of some novel "driver" genes, including SF3B1, NOTCH1, MYD88 and BIRC3 (Rossi et al, 2012(Rossi et al, , 2013. Despite the advance in the characterization of these genes, there is high genetic heterogeneity in CLL with several additional genes recurrently affected where no further analyses have been provided.…”
mentioning
confidence: 99%